Argyria and Neuropsychiatric Disorders: When not only the Matter is Gray. A Literature Review and a Case Report - Bonura, Adriano; Siniscalchi, Antonio; Crupi, Domenica; Magliozzi, Alessandro; Bravi, Maria Cristina; Internullo, Mattia; Mangiardi, Marilena; Pezzella, Francesca Romana; Schito, Barbara; Anticoli, Sabrina (Current Medicinal Chemistry, 2025)
Argyria is the chronic accumulation of silver in biological tissues such as skin, liver, kidneys, lungs, peripheral nerves, and brain. The presence of an actual pathophysiological and clinical correlate related to silver encephalic and peripheral nerve deposition is still much debated. In this paper, we reviewed and described case reports regarding argyria associated with neuropsychiatric symptoms in order to explain the underlying mechanism of the disease. We conducted a narrative review by searching for case reports that described subjects with chronic silver accumulation and who had associated neurological or psychiatric symptoms. Moreover, we report a case of a 50-year-old man admitted to our hospital with a diagnosis of major depression who presented with worsening psychiatric symptoms after abuse of silver-containing nasal spray. We found 15 cases of patients with argyria and neuropsychiatric manifestations such as epilepsy, neurodegenerative syndromes, multiple sclerosis, peripheral neuropathy, and psychiatric disorders. The knowledge of possible pathogenetic mechanisms and recognition of clinical features of argyria can help clinicians prevent brain deposition and its complications.
Keywords: adult patient